Process Mining Handbook - van der Aalst, Wil M. P.; Carmona, Josep; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This is an open access book. This book comprises all the single courses given as part of the First Summer School on Process Mining, PMSS 2022, which was held in Aachen, Germany, during July 4-8, 2022. The 17 chapters presented in this volume were organized in the following topical sections: introduction; process discovery; conformance checking; data preprocessing; process enhancement and monitoring; assorted process mining topics; industrial perspective and applications; and closing.
Introduction -- Process Mining: A 360 Degree Overview -- Process Discovery -- Foundations of Process Discovery -- Advanced Process Discovery Techniques -- Declarative Process Specifications: Reasoning, Discovery, Monitoring -- Conformance Checking -- Conformance Checking: Foundations, Milestones and Challenges -- Data Preprocessing -- Foundations of Process Event Data -- A Practitioner$1 (Bs View on Process Mining Adoption, Event Log Engineering and Data Challenges -- Process Enhancement and Monitoring -- Foundations of Process Enhancement -- Process Mining over Multiple Behavioral Dimensions with Event Knowledge Graphs -- Predictive Process Monitoring -- Assorted Process Mining Topics -- Streaming Process Mining -- Responsible Process Mining -- Industrial Perspective and Applications -- Status and Future of Process Mining: from Process Discovery to Process Execution -- Using Process Mining in Healthcare -- Process Mining for Financial Auditing -- Robotic Process Mining -- Closing -- Scaling Process Mining toTurn Insights Into Actions.s
Keywords: Information technology -- Management; Application software; Data mining; Business Process Management; Computer and Information Systems Applications; Data Mining and Knowledge Discovery; Computer Application in Administrative Data Processing